On Designing Time‐delay Feedback Controller for Master‐Slave Synchronization of Lur'e Systems. Issue 1 (25th January 2013) - Ji, Xiaofu; Ren, Mingwei; Su, Hongye
Abstract This paper is concerned with the problem of designing a time‐delay output feedback controller for master‐slave synchronization of Lur'e systems. The time delay is divided into two intervals and different energy functions are defined in each interval, which together provide a new Lyapunov–Krasovskii functional and derive a new delay‐dependent synchronization criterion. A sufficient condition for the existence of such a feedback controller is given, and an explicit expression of such a controller is also achieved. These algorithms are formulated in terms of linear matrix inequalities that can be solved easily. Chua's circuit is used to illustrate the effectiveness of the design method.